Customer satisfaction of urban farming application services: e-Buruan Sae - Parman Sukarno; Rio Guntur Utomo; Rahmat Yasirandi; Novian Anggis Suwastika (JURNAL INFOTEL, 2022)
This study evaluates the customer satisfaction model in adopting the Web 2.0-based e-Buruan Sae application. The e-Buruan Sae application is an interactive Web 2.0-based application used by the government and the people of Bandung City to manage urban farming activities. This research is quantitative correlational research and applies a research method based on Design Research Methodology (DRM). The stages of this research are the literature review stage with the output of research objectives, the initial empirical analysis stage with the outputs of the hypothesis and research model, the experimental stage for data collection, and the final empirical analysis stage with the output of the data analysis results. This study uses six variables to measure customer satisfaction: ease of use, service quality, interactivity, trust, customer satisfaction, and IT development. The results of empirical testing show that the ease of use and IT development variables do not affect the customer satisfaction variable. In contrast, the remaining variables have a positive effect on customer satisfaction. This research produces measurements to evaluate customer satisfaction on the Web 2.0-based urban farming application.